A PREFERRED LEADERSHIP PORTRAIT OF SUCCESSFUL CROSS-CULTURAL LEADERSHIP - CHOW, Tong Wooi; MOHD SALLEH, Lailawati; ISMAIL, Ismi Arif (Studia Universitatis Babeș-Bolyai Negotia, 2017)
Purpose: This article seeks to highlight the significance of the understanding of the cultural dimensions, global leadership attributes, and leadership profiles of the home culture of Malaysia in comparison to the adopted host culture of Canada to incorporate the best cross-cultural leadership practices. It presents the preferred leadership portrait of successful cross-cultural leadership. Findings: Cross-cultural competence has become a considerable important research in the last two decades. Cross-cultural studies on cross-cultural differences in leadership interaction of the home and host cultures of leaders are needed. It is appropriate to consider the preferred leadership portrait that adapts to the cultural dimensions, global leadership attributes, and leadership profiles of the leader’s home and host cultures for effective cross-cultural leadership practice. Research limitations/implications: The findings of this conceptual review paper need further study to validate the application of the adaptation of the cultural dimensions, global leadership attributes, and leadership profiles of the related home and host countries based on the GLOBE study. Practical implications: There are values in the understanding of the application of cross-cultural principles based on cross-cultural research information for cross-cultural leadership adaptation and practices. The knowledge of the related leadership, cultural factors will facilitate cross-cultural understanding and interrelation. Leaders today are to develop the competencies to be effective in the globally connected societies as well. Originality/value: This paper on cross-cultural leadership used findings based on the GLOBE studies as the main text to understand the various cultural factors that have an impact on leadership. The information on the cultural dimensions, global leadership attributes, and leadership profiles of the home and adopted host countries were compared and contrasted to construct the best approach for cross-cultural leadership practices. The concept of the preferred leadership portrait is in congruent to the leadership, sustainability concept that promotes the long term view and progress of leaders, systems, and organizations. JEL Classification: M16